Simply Fuzzy generalized open and closed sets - Noaman, I.; Sayed, M. El (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we introduced new concepts , Simply open set, Simply fuzzy open set, Simply fuzzy continuous, Simply fuzzy open function( resp. fuzzy –closed ), simply fuzzy open cover and simply fuzzy compact. We study some of their properties.